The expansion of royal caribbean cruises - Fernandes, Mafalda Erbert Silva Mango (2020)
The present master thesis “The Expansion of Royal Cruises ”was developed in order to give investors’ a recommendation about Royal Caribbean Cruises, Ltd. Royal Caribbean Ltd. is the second largest cruise line, behind Carnival Corp. Although the company was settled since 1968, it continues to innovate and keep up with new trends. RCL will expand substantially its fleet, following the prospects of future growth in the global ocean passengers carried, world de. A deep analysis was performed regarding RCL’s industry, competitors, business model, trends, financial situation, etc. which was reflected in our valuation through the Discounted Cash Flow model.